Interfacial reacions of Ni on Si1-xGex (x=0.2, 0.3) at low temperature by rapid thermal annealing - Pey, Kin Leong (2012)
The interfacial reaction of Ni with relaxed Si1-xGex (x=0.2,0.3) films in the low temperature range,